IFN-γ Response Is Associated to Time Exposure Among Asymptomatic Immune Responders That Visited American Tegumentary Leishmaniasis Endemic Areas in Peru - Best, Ivan; Privat-Maldonado, Angela; Cruz, María; Zimic, Mirko; Bras-Gonçalves, Rachel; Lemesre, Jean-Loup; Arévalo, Jorge (Frontiers in Cellular and Infection Microbiology, 2018)
Clinical manifestations of American Tegumentary Leishmaniasis (ATL) include cutaneous (CL) and mucous forms (ML); however, there are asymptomatic individuals who despite being infected do not present any clinical manifestations. This study characterized the cell-mediated immunity of travelers who lived in the Andean highlands of Cusco, free of leishmaniasis transmission, which eventually visited leishmaniasis endemic in the Amazonian basin and returned home without any clinical signs of the disease. Their immune response was compared with CL and ML patients who acquired the disease during their stage in the same region. Fifty-four human subjects from the highlands of Cusco (Peru), who have visited an endemic area, were enrolled: 28 of them did not show any symptoms, 12 showed CL and 14 showed ML. Ten healthy subjects from a non-endemic area (HS) were included as controls. T-cell proliferation was evaluated using peripheral blood mononuclear cells (PBMC) stimulated for 5 days with a total soluble leishmanial antigen (TSLA) of L. (V.) braziliensis. Th1/Th2/Th17 cytokines were also quantified in the supernatants by a flow cytometry multiplex assay. T-cell proliferation was expressed as stimulation index (SI) and the cut off was fixed at SI > 2.47. Fifteen out of 28 subjects did not show any signs of disease (54%); subjects with an SI above the cut off. They were defined as asymptomatic immune responders (AIR). CL and ML patients presented a higher SI than HS and AIR. Among the latter group, the exposure time to Leishmania was clearly associated with the IFN-γ response. Increased levels of this cytokine were observed in individuals who remained less than 90 days in an endemic area of leishmaniasis. Our results evidenced two sub-populations among asymptomatic individuals, one AIR who did not develop clinical disease manifestations when they were exposed to Leishmania in endemic areas. Exposure time to Leishmania in the wild was associated with the IFN-γ response.